Attitudes toward the Use of TELL Tools in English Language Learning among Vietnamese Tertiary English Majors - Tran Quoc Thao; Duong My Tham; Huynh Thi Thien Ngan, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Technology plays a crucial role in the self-guided learning of a second language in general and English in particular. Nevertheless, many students in different contexts still ignore the application of technology-enhanced language learning (TELL) tools in enhancing their foreign language proficiency. Therefore, this study is conducted to investigate the attitudes towards the use of TELL tools in English-language learning (ELL) among English majors at one university in Vietnam. To collect data, 197 English majors participated in finishing the questionnaire, and 20 students were invited to join the interviews. The findings are that the majority of students have positive attitudes towards the use of TELL tools and the frequency of using these tools is very high. In addition, the results also reveal that there is no significant difference in attitudes towards and frequency of using TELL tools in learning English in terms of the year of study. However, students of different levels of academic achievements have different attitudes towards using TELL tools and use TELL tools to learn English differently.Received 2nd May 2019; Revised 16th July 2019; Accepted 20th October 2019